INNOVATION PRODUCTION MODELS - T. N. Guseinova (Vestnik MGIMO-Universiteta)
The article is dedicated to the study of the models of production of innovations at enterprise and state levels. The shift towards a new technology wave induces a change in systems of division of labour as well as establishment of new forms of cooperation that are reflected both in theory and practice of innovation policy and management. Within the scope of the research question we have studied different generation of innovation process, starting with simple linear models - "technology push" and "market pull" - and ending with a complex integrated model of open innovations. There are two organizational models of innovation production at the enterprise level: start-ups in the early stages of their development and ambidextrous organizations. The former are prone to linear models of innovation process, while the latter create innovation within more sophisticated inclusive processes. Companies that effectuate reciprocal ambidexterity stand out from all the rest, since together with start-ups, research and development centres, elements of innovation infrastructure and other economic agents operating in the same value chain they constitute the core of most advanced forms of national innovation systems, namely Triple Helix and Quadruple Helix systems. National innovation systems - models of innovation production at the state level - evolve into systems with a more profound division of labour that enable "line production" of innovations. These tendencies are closely related to the advent and development of the concept of serial entrepreneurship that transforms entrepreneurship into a new type of profession. International experience proves this concept to be efficient in various parts of the world. Nevertheless, the use of above mentioned models and concepts in national innovation system should be justified by socioeconomic conditions of economic regions, since they determine the efficiency of implementation of certain innovation processes and organizational designs at company and national system level.